Design and Development of Information Systems Supporting Stock Investors "Batch of Automatic Stock Analysis System" - Dipta Harimbawa; Moh. Hasanudin; Bagas Putra Pradana; Afiat Sadida (Ilomata International Journal of Management, 2022)
Many information systems make it easier for stock investors to make decisions to buy shares. But no information system provides an easy-to-understand display and exclusive features to make it easier for investors to make decisions and find information about stock investments, especially for novice investors. Therefore, this study aims to design and build a web-based information system that can assist stock investors in making decisions and seeking information about stock investments. The design of this information system is equipped with a stock overview, moving average analysis, analysis of Minervini trends templates, analysis of candlestick patterns, stock screeners, and stock lists. Stocks that can be analyzed using technical analysis and candlestick patterns are only stocks belonging to the LQ45, KOMPAS100, IDX80, IDX30, JII70, Investor33, Pefindo25 constituents. The results of this study are stock investors can get stock recommendations in real-time and information about stock investments quickly.